Auxiliary cementitious material for efficient carbon fixation based on two-step method and preparation method and application thereof
By adopting a two-step method in the cement industry, using calcium carbide slag and low-calcium fly ash to pretreat with EDTA and react with carbon dioxide industrial waste gas, high-efficiency carbon-solid gelling materials are prepared, and the existing carbon-solid gelling materials are solved. The problems of low carbon dioxide storage efficiency and high carbon emissions in the cement industry in the technology have achieved efficient and low energy consumption carbon storage and material strength improvement.
Patent Information
- Application Number
- CN202410110524.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-26
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-01-26
AI Technical Summary
The existing carbon dioxide storage methods are inefficient, energy-consuming and time-consuming, and the problem of high carbon emissions in the cement industry has not been effectively solved.
Using a two-step method, using calcium carbide slag as calcium source and low-calcium fly ash as adsorption carrier and calcium source, low-calcium fly ash is pretreated by ethylenediaminetetraacetic acid (EDTA), and with calcium carbide slag Mix and use industrial waste gas containing carbon dioxide for carbonization to prepare an auxiliary gelling material that is efficient carbon-solidated.
It has achieved high efficiency and low energy consumption carbon sequestration, high carbon dioxide storage and storage efficiency, and resource reuse of fly ash and calcium carbide slag. The resulting gelled material has higher strength and faster settling time, which can replace part of the cement. , reduce carbon emissions.
Smart Images

Figure BDA0004683206590000081 
Figure BDA0004683206590000082 
Figure BDA0004683206590000091
Abstract
Description
Technical Field
[0001] The invention relates to an auxiliary cementitious material for efficient carbon fixation based on a two-step method and a preparation method and application thereof, belonging to the technical field of building materials. Background Art
[0002] With the development of science and technology, the amount of heat-absorbing greenhouse gases such as carbon dioxide emitted into the atmosphere by humans has increased year by year, and the greenhouse effect of the atmosphere has also increased, which has caused a series of extremely serious problems such as global warming and has attracted the attention of countries around the world. As the most important greenhouse gas, carbon dioxide emissions are in urgent need of effective control. However, existing carbon dioxide storage methods have problems such as low efficiency, high energy consumption, and long time consumption. In addition, the cement industry is a high-carbon emission industry. From the perspective of global economic development, carbon emissions from cement production will continue to rise. Therefore, it is urgent to develop low-carbon cementitious materials to replace cement or part of cement to further reduce carbon dioxide emissions.
[0003] Fly ash is the fine ash collected from the flue gas after coal combustion. It is the main solid waste discharged by coal-fired power plants. With the development of the power industry, the amount of fly ash discharged from coal-fired power plants has increased year by year, becoming one of the largest industrial waste residues in my country. If a large amount of fly ash is not treated, it will produce dust and pollute the atmosphere; if it is discharged into the water system, it will cause river siltation, and the toxic chemicals in it will also cause harm to humans and organisms; if it is stored in a landfill, improper treatment will pollute water sources and soil. Calcium carbide slag is the waste residue produced by the production of acetylene by the calcium carbide method. The amount of calcium carbide slag is large, the alkali content is high, and it contains harmful substances such as sulfur and arsenic. If it is discharged without treatment, it will clog the sewer, accumulate the riverbed, and endanger fishery production; if it is piled up on land, it will occupy land and pollute the environment.
[0004] Carbon dioxide mineralization and storage is an optional solution for the disposal of alkaline industrial solid wastes such as fly ash and carbide slag. Carbon dioxide mineralization and storage can fix carbon dioxide in an environmentally friendly, safe and permanent manner. At the same time, the solid waste raw materials are abundant in source, huge in reserves and low in price. The mineralized products can also be further used as mineral admixtures, etc., which has the potential for large-scale fixation and good economic benefits. However, low-calcium fly ash has a low calcium content and limited carbon fixation capacity. When carbide slag is carbonized alone, the generated calcium carbonate is in situ aggregated and distributed on the surface of the carbide slag particles. Even under high temperature and high pressure conditions, Ca 2+ The leaching is still slowed down, which makes the carbonization reaction time too long and greatly reduces the economic benefits.
[0005] The present invention is proposed to solve the above-mentioned problems. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides an auxiliary cementitious material with high efficiency in carbon fixation based on a two-step method, and a preparation method and application thereof. The present invention uses carbide slag as a calcium source, low-calcium fly ash as an adsorption carrier and calcium source, and uses ethylenediaminetetraacetic acid (EDTA) to pretreat the low-calcium fly ash, and then mixes the pretreated low-calcium fly ash with carbide slag and reacts with industrial waste gas containing carbon dioxide to prepare a cementitious material. The raw materials of the method of the present invention are cheap and easy to obtain, with high efficiency and low energy consumption; the calcium element inside the fly ash and carbide slag can fully react in a short time, and the carbon dioxide in the industrial waste gas can be permanently sealed, and the carbon dioxide sealing amount and sealing efficiency are high; the resource recycling of fly ash and carbide slag waste is fully realized. The cementitious system prepared by compounding the obtained cementitious material and cement has higher strength and faster setting time, and is expected to replace more cement clinker to prepare low-carbon composite cement.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step method, comprising the steps of:
[0009] (1) low-calcium fly ash and ethylenediaminetetraacetic acid (EDTA) powder are uniformly mixed, industrial waste gas containing carbon dioxide and water vapor is continuously introduced, and the mixture is dried to obtain pretreated low-calcium fly ash after carbonization reaction;
[0010] (2) Pretreated low-calcium fly ash, carbide slag and water are mixed evenly, and industrial waste gas containing carbon dioxide and water vapor is continuously introduced into the reaction materials to undergo carbonization reaction, followed by filtration and drying to obtain an auxiliary cementitious material for efficient carbon fixation based on a two-step method.
[0011] Preferably according to the present invention, in step (1), the low-calcium fly ash is solid waste generated by a coal-fired power plant, and the particle size of the low-calcium fly ash is 400-500 mesh.
[0012] Preferably according to the present invention, in step (1), the low-calcium fly ash comprises the following components in parts by mass: 2.32-3.76 parts of CaO, 44.01-57.89 parts of SiO2, 23.24-31.34 parts of Al2O3, 2.27-5.15 parts of Fe2O3, and 0.63-3.97 parts of MgO.
[0013] Preferably according to the present invention, in step (1), the mass of ethylenediaminetetraacetic acid (EDTA) is 0.5-2% of the mass of calcium in the low-calcium fly ash.
[0014] Preferably, according to the present invention, in step (1), the continuous introduction rate of the industrial waste gas containing carbon dioxide and water vapor is 3-5 L / min.
[0015] Preferably, according to the present invention, in step (1), the industrial waste gas containing carbon dioxide and water vapor comprises the following components in volume percentage: water vapor 8-11%, carbon dioxide 25-27%, and nitrogen 59-61%; preferably, the industrial waste gas containing carbon dioxide and water vapor comprises the following components in volume percentage: water vapor 10.7%, carbon dioxide 26.9%, and nitrogen 59.1%.
[0016] Preferably, in step (1), the carbonization reaction time is 3-7 min, preferably 5 min; the carbonization reaction temperature is 20-30° C., and the pressure is 0.05-0.5 MPa.
[0017] Preferably according to the present invention, in step (2), the carbide slag is solid waste generated by an acetylene gas plant, and the particle size of the carbide slag is 1000 mesh to 1200 mesh.
[0018] Preferably according to the present invention, in step (2), the carbide slag comprises the following components in parts by weight: 86.26 to 89.21 parts of CaO, 3.12 to 5.41 parts of SiO2, 4.01 to 6.75 parts of SO3, 1.39 to 2.27 parts of Al2O3, and 0.21 to 1.97 parts of MgO.
[0019] Preferably, according to the present invention, in step (2), the mass ratio of the pretreated low-calcium fly ash to the carbide slag is 60-90:10-30.
[0020] According to the preferred embodiment of the present invention, in step (2), the liquid-to-solid ratio of the mixture of pretreated low-calcium fly ash, carbide slag and water is 5-10 ml / g, preferably 7.5 ml / g. The solid in the liquid-to-solid ratio refers to the pretreated low-calcium fly ash and carbide slag.
[0021] Preferably, according to the present invention, in step (2), the continuous introduction rate of the industrial waste gas containing carbon dioxide and water vapor is 3-5 L / min.
[0022] Preferably, according to the present invention, in step (2), the industrial waste gas containing carbon dioxide and water vapor comprises the following components in volume percentage: water vapor 8-11%, carbon dioxide 25-27%, and nitrogen 59-61%; preferably, the industrial waste gas containing carbon dioxide and water vapor comprises the following components in volume percentage: water vapor 10.7%, carbon dioxide 26.9%, and nitrogen 59.1%.
[0023] Preferably, in step (2), the carbonization reaction time is 10-15 min, preferably 12 min; the carbonization reaction is carried out under stirring conditions, and the stirring rate is 300-500 r / min, preferably 400 r / min; the carbonization reaction temperature is 20-30°C, and the pressure is 0.05-0.15 MPa.
[0024] An auxiliary cementitious material with high efficiency of carbon fixation based on a two-step method is prepared by the above method.
[0025] Application of the above-mentioned auxiliary cementitious material with high carbon fixation efficiency based on the two-step method in concrete and / or mortar.
[0026] Preferably, according to the present invention, the cementitious material and cement are compounded and applied to concrete and / or mortar; preferably, the mass ratio of the cementitious material to cement is 20-40:60-80. The cementitious material of the present invention can replace part of the cement, reduce the carbon footprint of the cement industry, and alleviate the impact of greenhouse gases on the environment. At the same time, the calcium carbonate generated by the carbonization reaction can accelerate the hydration of cement and improve the early strength of cement-based materials.
[0027] The principle of carbonation reaction is:
[0028] The carbonation reaction involves a series of physical and chemical processes. Based on the gas-liquid-solid three-phase reaction theory, it can be roughly divided into four stages. First, the calcium-based active substances in carbide slag and fly ash dissolve, hydrolyze in water, release hydroxide ions, and increase the pH value of the slurry. The strong alkalinity of the slurry can efficiently capture carbon dioxide in industrial waste gas; the carbon dioxide in the industrial waste gas dissolves in water to form carbonic acid, which reacts rapidly with hydroxide ions and calcium ions in the slurry, causing the pH value of the slurry to begin to decrease and form calcium carbonate precipitation; as the mineralization reaction continues, the rate of hydrolysis to produce hydroxide ions gradually decreases below the rate of carbon dioxide to produce hydrogen ions. When the pH value of the slurry gradually decreases to 7 and remains unchanged, the carbonation reaction is basically completed.
[0029] CaO+H2O=Ca(OH)2
[0030] Ca(OH)2=Ca 2+ +2OH -
[0031]
[0032]
[0033]
[0034]
[0035] Ca 2+ +CO3 2- =CaCO3
[0036] The technical features and beneficial effects of the present invention are:
[0037] 1. The present invention uses carbide slag as a calcium source and low-calcium fly ash as an adsorption carrier and calcium source. First, the low-calcium fly ash is pretreated, mixed with ethylenediaminetetraacetic acid (EDTA), and reacted with the introduced carbon dioxide and water vapor; in the presence of a small amount of water, part of the CaO dissolves in the water to generate Ca 2+ , EDTA and Ca dissolved in water 2+ The EDTA-Ca chelate generated by chelation adheres to the surface of fly ash. After direct dry carbonization, the EDTA-Ca chelate reacts with carbon dioxide to obtain calcium carbonate, and EDTA is released back into the water to obtain pretreated low-calcium fly ash. The present invention performs pretreatment through direct dry carbonization reaction, so that the surface of fly ash is covered with nano calcium carbonate with a particle size of 10-30nm, the specific surface area is increased, and the subsequent nucleation sites of calcium carbonate are increased, which is beneficial to the smooth generation of subsequent calcium carbonate and the continued growth of subsequent calcium carbonate at the nucleation sites. Subsequently, in the wet carbonization process, the pretreated low-calcium fly ash is mixed with carbide slag and water; the EDTA therein continues to react with the Ca carbonate dissolved in the water. 2+ The EDTA-Ca chelate generated by chelation promotes the leaching of calcium ions in carbide slag. The EDTA-Ca chelate reacts with the carbonate ions generated by the dissolution of carbon dioxide and preferentially generates calcium carbonate at the calcium carbonate nucleation sites. At the same time, as the amount of calcium ion leaching increases, the amount of free calcium ions increases, and the carbonate ions generated by the dissolution of carbon dioxide directly react with the Ca in the water. 2+ The calcium carbonate is first generated at the calcium carbonate nucleation site; most of the newly generated calcium carbonate grows on the surface of the pre-treated calcium carbonate; and finally, the gelling material is obtained after filtration and drying. The addition of ethylenediaminetetraacetic acid (EDTA) in the present invention promotes the leaching of calcium ions, improves the carbonization efficiency, and generates more calcium carbonate.
[0038] 2. Carbide slag is the main source of calcium. When it is carbonized alone, the calcium carbonate generated by the reaction is in-situ aggregated and distributed on the surface of the carbide slag particles, which slows down the Ca 2+ In the present invention, the low-calcium fly ash pretreated by direct dry carbonization is covered with nano-calcium carbonate with a particle size of 10-30nm, and the nucleation sites of calcium carbonate are increased. The subsequent wet carbonization has a synergistic carbonization effect. The produced calcium carbonate will grow at the calcium carbonate nucleation sites of the low-calcium fly ash, which is beneficial to the Ca in carbide slag. 2+ With the continuous leaching of carbon dioxide, the storage capacity and efficiency of carbon dioxide are greatly improved.
[0039] 3. The method of the present invention uses industrial solid wastes such as fly ash and carbide slag, and the raw materials are cheap and easily available, so that fly ash and carbide slag can be efficiently recycled and reused, turning waste into treasure. The method of the present invention uses industrial waste gas containing carbon dioxide as a carbon source, fully utilizes carbon dioxide waste gas, realizes effective storage of carbon dioxide, and also realizes resource recycling, avoiding the harm caused by the emission of carbon dioxide into the atmosphere.
[0040] 4. The raw materials of the method of the present invention are cheap and readily available, with high efficiency and low energy consumption; the carbon dioxide in industrial waste gas can be permanently sealed, and the carbon dioxide sealing amount and sealing efficiency are high; the resource recycling of fly ash and carbide slag waste is fully realized. The cementitious system prepared by compounding the obtained cementitious material with cement has higher strength and faster setting time, and is expected to replace more cement clinker to prepare low-carbon composite cement.
[0041] 5. As a whole, the method of the present invention requires each step and each condition to work together to achieve the effect of the present invention. In the preparation of the pretreated low-calcium fly ash of the present invention, the ratio of low-calcium fly ash and ethylenediaminetetraacetic acid (EDTA) needs to be appropriate. If it is not appropriate, it will affect the Ca 2+ The leaching amount and the crystal size of calcium carbonate on the surface cause the reaction efficiency of the second step wet carbonization to decrease, and the performance of the obtained cementitious material to decrease; the EDTA of the present invention has specificity, and if it is replaced by a similar substance, the performance of the obtained cementitious material will also decrease; the ratio of the pretreated low-calcium fly ash, carbide slag and water in the present invention needs to be appropriate. If it is not appropriate, it will affect the Ca content in the raw materials. 2+ The leaching of ions and the growth of calcium carbonate on the surface of fly ash affect the content of calcium carbonate generated by the carbonization reaction, and further affect the performance of the cementitious material; during the wet carbonization process of the present invention, the stirring speed needs to be appropriate. If the speed is too slow, the reaction is slow, and if the speed is too fast, the calcium carbonate cannot grow completely to the nucleation site. DETAILED DESCRIPTION
[0042] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, they will be described in detail below in conjunction with specific embodiments, but are not limited to these. Anything not fully described in the present invention shall be based on conventional techniques in the art.
[0043] In the embodiment, the carbide slag powder includes the following components in percentage by weight: CaO 88.10wt%, SiO2 3.51wt%, SO3 5.77wt%, Al2O3 1.91wt%, and MgO 0.35wt%.
[0044] The low-calcium fly ash includes the following components in percentage by mass: CaO 2.56wt%, SiO2 57.25wt%, Al2O3 23.24wt%, Fe2O3 5.02wt%, and MgO 1.97wt%.
[0045] The industrial waste gas containing carbon dioxide and water vapor includes the following components in volume percentage: water vapor 10.7%, carbon dioxide 26.9%, nitrogen 59.1%, and other components 3.3%.
[0046] Example 1
[0047] A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step method, comprising the steps of:
[0048] (1) low-calcium fly ash (400-500 mesh) and ethylenediaminetetraacetic acid (EDTA) powder are mixed in a mixer for 5 minutes and then added into a reactor, wherein the mass of EDTA is 1% of the mass of calcium in the low-calcium fly ash, industrial waste gas containing carbon dioxide and water vapor is continuously introduced into the reactor at a rate of 4 L / min, reacted at 25° C. and 0.1 MPa for 5 minutes, and then dried to obtain pretreated low-calcium fly ash;
[0049] (2) Pretreated low-calcium fly ash, carbide slag (1000 mesh to 1200 mesh) and water are mixed uniformly, wherein the mass ratio of the pretreated low-calcium fly ash to carbide slag is 80:20, and the liquid-solid ratio is 7 ml / g; the stirring rate is 300 r / min, the temperature is controlled at 25°C, the pressure is controlled at 0.1 MPa, and industrial waste gas containing carbon dioxide and water vapor is continuously introduced at a rate of 4 L / min to carry out carbonization reaction for 12 minutes; after filtering and drying, an auxiliary cementitious material with high-efficiency carbon fixation based on the two-step method is obtained.
[0050] Example 2
[0051] A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step process is as described in Example 1, except that in step (2), the stirring rate is 400 r / min; the other steps and conditions are the same as in Example 1.
[0052] Example 3
[0053] A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step process is as described in Example 1, except that in step (2), the stirring rate is 500 r / min; the other steps and conditions are the same as in Example 1.
[0054] Example 4
[0055] A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step process is as described in Example 2, except that in step (2), the liquid-to-solid ratio is 7.5 ml / g; the other steps and conditions are the same as in Example 2.
[0056] Example 5
[0057] A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step process is as described in Example 2, except that in step (2), the liquid-to-solid ratio is 8 ml / g; the other steps and conditions are the same as in Example 2.
[0058] Example 6
[0059] A method for preparing an auxiliary cementitious material with high-efficiency carbon fixation based on a two-step process is as described in Example 4, except that in step (2), the mass ratio of pretreated low-calcium fly ash to carbide slag is 70:30; the other steps and conditions are the same as in Example 4.
[0060] Example 7
[0061] A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step process is as described in Example 4, except that in step (1), the mass of ethylenediaminetetraacetic acid is 2% of the mass of calcium contained in low-calcium fly ash; the other steps and conditions are the same as in Example 4.
[0062] Example 8
[0063] A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step process is as described in Example 4, except that in step (1), the mass of ethylenediaminetetraacetic acid is 0.5% of the mass of calcium contained in low-calcium fly ash; the other steps and conditions are the same as in Example 4.
[0064] Comparative Example 1:
[0065] A method for preparing a cementitious material, as described in Example 4, except that: EDTA is not added in step (1); the specific steps are as follows: low-calcium fly ash (400-500 mesh) is put into a reactor, industrial waste gas containing carbon dioxide and water vapor is continuously introduced into the reactor at a rate of 4 L / min, reacted at 25° C. and 0.1 MPa for 5 min, and then dried to obtain pretreated low-calcium fly ash;
[0066] The other steps and conditions are the same as in Example 4.
[0067] Comparative Example 2
[0068] A method for preparing a gelling material is as described in Example 4, except that in step (1), ethylenediaminetetraacetic acid is replaced by ethylene glycol diethyl ether diaminetetraacetic acid (EGTA); the other steps and conditions are the same as in Example 4.
[0069] Comparative Example 3
[0070] A method for preparing a gelling material comprises the following steps:
[0071] Low-calcium fly ash (400-500 mesh), ethylenediaminetetraacetic acid (EDTA) powder, carbide slag (1000-1200 mesh) and water are uniformly mixed, wherein the mass of ethylenediaminetetraacetic acid is 1% of the mass of calcium contained in the low-calcium fly ash, the mass ratio of low-calcium fly ash to carbide slag is 80:20, and the liquid-solid ratio is 7.5 ml / g (wherein the solid refers to low-calcium fly ash, ethylenediaminetetraacetic acid (EDTA) and carbide slag); the stirring rate is 400 r / min, the temperature is controlled at 25°C, the pressure is controlled at 0.1 MPa, and industrial waste gas containing carbon dioxide and water vapor is continuously introduced at a rate of 4 L / min to carry out carbonization reaction for 12 minutes; and a cementitious material is obtained by filtering and drying.
[0072] Test Example 1
[0073] The carbon dioxide storage capacity of the gelling materials prepared in Examples 1-8 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1. The carbon dioxide storage capacity of the gelling materials was obtained by a thermogravimetric analyzer. At 600°C to 800°C, CaCO3 produced by carbonization decomposed into CaO and CO2, and the carbon dioxide storage capacity was obtained by weight loss.
[0074] Table 1 Carbon dioxide storage capacity of the gelling materials prepared in Examples 1 to 8 and Comparative Examples 1 to 3
[0075]
[0076]
[0077] Test Example 2
[0078] The standard mortar mechanical properties of the cementitious materials prepared in Examples 1-8 and Comparative Examples 1-3 were tested, and the test results are shown in Table 2 below. Experimental conditions: 135 g of cementitious material and 315 g of PI 42.5 cement were mixed as a cementitious system, and mixed with 225 g of water and 1350 g of ISO sand according to the "Technical Specification for Application of Mineral Admixtures" (GB / T 51003-2014). According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021), after the specimen was demoulded, it was placed in water at 20°C ± 1°C for curing for 28 days.
[0079] At the same time, a control group was set up, namely:
[0080] Low-calcium fly ash / PI 42.5 cement group: 135 g of low-calcium fly ash (same composition as in the above example) and 315 g of PI 42.5 cement were mixed to form a cementitious system; other experimental methods were the same as above, and the 28d compressive strength was tested.
[0081] PI 42.5 cement group: 450 g of PI 42.5 cement was used as the cementitious system; other experimental methods were the same as above, and the 28d compressive strength was tested.
[0082] Table 2 Mechanical properties of standard mortars of cementitious materials prepared in Examples 1-8 and Comparative Examples 1-3
[0083]
[0084]
[0085] Test Example 3
[0086] The standard consistency water consumption and initial and final setting time of the cementitious materials prepared in Examples 1-8 and Comparative Examples 1-3 were tested, and the test results are shown in Table 3. Experimental conditions: 150 g of cementitious material and 350 g of PI 42.5 cement were mixed as a cementitious system, and the standard consistency water consumption was obtained according to the "Test Method for Standard Consistency Water Consumption, Setting Time and Stability of Cement" (GB / T 1346-2011), and the initial and final setting time of the cementitious material were obtained according to the standard consistency water consumption.
[0087] At the same time, a control group was set up, namely:
[0088] Low calcium fly ash / PI 42.5 cement group: 150 g of low calcium fly ash (same composition as in the above embodiment) and 350 g of PI 42.5 cement were mixed as the cementitious system; other experimental methods were the same as above, and the water consumption for standard consistency, as well as the initial and final setting times were tested.
[0089] PI 42.5 cement group: 500 g of PI 42.5 cement was used as the cementitious system; other experimental methods were the same as above, and the water consumption for standard consistency, as well as the initial and final setting times were tested.
[0090] Table 3 Standard consistency water consumption and initial and final setting time of the cementitious materials prepared in Examples 1-8 and Comparative Examples 1-3
[0091]
[0092]
[0093] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing an auxiliary cementitious material for efficient carbon fixation based on a two-step method, comprising the steps of: (1) low-calcium fly ash and ethylenediaminetetraacetic acid (EDTA) powder are uniformly mixed, industrial waste gas containing carbon dioxide and water vapor is continuously introduced, and the mixture is dried to obtain pretreated low-calcium fly ash after carbonization reaction; The mass of ethylenediaminetetraacetic acid (EDTA) is 0.5-2% of the mass of calcium in low-calcium fly ash; (2) Pre-treated low-calcium fly ash, carbide slag and water are uniformly mixed, industrial waste gas containing carbon dioxide and water vapor is continuously introduced into the reaction materials, carbonization reaction is carried out, and then filtering and drying are performed to obtain an auxiliary cementitious material with high efficiency carbon fixation based on a two-step method; The mass ratio of pretreated low-calcium fly ash to carbide slag is 60~90:10~30; the liquid-solid ratio of the mixture of pretreated low-calcium fly ash, carbide slag and water is 5-10ml / g; the carbonization reaction is carried out under stirring conditions, and the stirring rate is 300~500r / min.
2. The method for preparing the auxiliary cementitious material for efficient carbon fixation based on the two-step method according to claim 1 is characterized in that: In step (1), one or more of the following conditions are included: i. The particle size of low calcium fly ash is 400-500 mesh; ii. Low-calcium fly ash includes the following components in parts by mass: 2.32~3.76 parts of CaO, 44.01~57.89 parts of SiO2, 23.24~31.34 parts of Al2O3, 2.27~5.15 parts of Fe2O3, and 0.63~3.97 parts of MgO.
3. The method for preparing the auxiliary cementitious material for efficient carbon fixation based on the two-step method according to claim 1 is characterized in that: In step (1), one or more of the following conditions are included: i. The continuous introduction rate of industrial waste gas containing carbon dioxide and water vapor is 3-5L / min; ii. Industrial waste gas containing carbon dioxide and water vapor includes the following components in volume percentage: water vapor 8-11%, carbon dioxide 25-27%, nitrogen 59-61%; iii. The carbonization reaction time is 3-7 minutes; the carbonization reaction temperature is 20-30°C, and the pressure is 0.05-0.5MPa.
4. The method for preparing the auxiliary cementitious material for efficient carbon fixation based on the two-step method according to claim 1 is characterized in that: In step (2), one or more of the following conditions are included: i. The particle size of carbide slag is 1000 mesh ~ 1200 mesh; ii. Carbide slag includes the following components by mass: 86.26-89.21 parts of CaO, 3.12-5.41 parts of SiO2, 4.01-6.75 parts of SO3, 1.39-2.27 parts of Al2O3, and 0.21-1.97 parts of MgO; iii. The continuous introduction rate of industrial waste gas containing carbon dioxide and water vapor is 3-5L / min; iv. Industrial waste gas containing carbon dioxide and water vapor includes the following components in volume percentage: water vapor 8-11%, carbon dioxide 25-27%, nitrogen 59-61%; v. The carbonization reaction time is 10-15 min; the stirring rate is 400 r / min; the carbonization reaction temperature is 20-30°C and the pressure is 0.05-0.15 MPa.
5. An auxiliary cementitious material for efficient carbon fixation based on a two-step method, prepared by the method described in any one of claims 1 to 4.
6. Use of the auxiliary cementitious material with high carbon fixation efficiency based on the two-step method as claimed in claim 5 in concrete and / or mortar.
7. The use according to claim 6, characterized in that: The cementitious material and cement are compounded and applied to concrete and / or mortar; the mass ratio of the cementitious material to the cement is 20-40:60-80.
Citation Information
Patent Citations
Method for modifying, upgrading and carbon dioxide mineralization emission reduction of circulating fluidized bed fly ash, modified fly ash and application of modified fly ash
CN114477825A
Method for preparing non-autoclaved aerated concrete brick by wet grinding and carbon sequestration of carbide slag
CN115215586A